IMPLEMENTASI SEO (SEARCH ENGINE OPTIMIZATION) ON PAGE UNTUK MENINGKATKAN PENGUNJUNG WEBSITE XTRAORDINARY - Adrian Suwardi; Husni Angriani; Afifah (KHARISMA Tech, 2022)
Private course is an informal institution that allows students to get additional lesson in order to enhance theirs understanding on certain subject. Most parents rely on professional services to help their children in learning. Xtraordinary Website is one of websites that provides private tutors which is can be accessed through page https://www.xtraordinarytutor.com. According to the results of Google Analytics monitoring that the website since its first launch, it has not had visitors. The implementation of SEO On Page is carried to increase the number of visitors. The implementation of SEO On page includes Title Tags, Meta Descriptions, Meta Keywords, Meta Headings, and Meta Images. The result indicated the effectiveness of SEO On Page in achieving faster result in short time. Increase in visitors’ traffic on Xtraordinary website is showed by the implementation of SEO On Page. As the effect of implementation also placed the Xtraordinary website as first rank on search engine with keywords related to private tutors.